Origin of the PSEN1 E280A mutation causing early–onset Alzheimer’s disease (2014)
ABSTRACT: Background: A mutation in presenilin 1 (E280A) causes early-onset Alzheimer's disease. Understanding the origin of this mutation will inform medical genetics. Methods: We sequenced the genomes of 102 individuals from Antioquia, Colombia. We applied identity-by-descent analysis to identify regions of common ancestry. We estimated the age of the E280A mutation and the local ancestry of the haplotype harboring this mutation. Results: All affected individuals share a minimal haplotype of 1.8 Mb containing E280A. We estimate a time to most recent common ancestor of E280A of 10 (95% credible interval, 7.2-12.6) generations. We date the de novo mutation event to 15 (95% credible interval, 11-25) generations ago. We infer a western European geographic origin of the shared haplotype. Conclusions: The age and geographic origin of E280A are consistent with a single founder dating from the time of the Spanish Conquistadors who began colonizing Colombia during the early 16th century. Keywords: Alzheimer’s disease; PSEN1; population genetics; whole-genome sequencing.